Electromagnetics and Network Theory and their Microwave Technology Applications - Weigel, Robert; Lindenmeier, Stefan (Springer-Verlag, 2011)
This book gives a compact overview about actual research in the field of Electromagnetics and Network Theory and its Microwave Applications. It contains aspects on antennas and wave propagation, microwave- and communication-systems and methods for the numerical modeling of components, networks and structures being part of these systems. An actual state of research in antennas and propagation is given as well as wave propagation in RF-lines and electric networks which are crucial for the investigation of microwave systems like radar-, radio-location- and communication- systems. Especially in mobile applications, radar- , radio-location- and navigation- systems as well as microwave sensors are more and more in use. Therefore an actual state of research in this field is given. Actual results of research on such systems are shown for automotive radar, a high precision radio-location-system, RF-sensors and RF-measurement technologies. The wide field of communication systems is further discussed where an overview about progress in mobile communication and wireless data transmission is given and results of actual research are shown. At last, actual numerical methods are discussed which are essential for the estimation of electromagnetic effects in all the applications shown previously. In the scope between the treatment of very tiny structures and very large structures new ways are shown for the numerical modeling of the electromagnetic field in nanostructures as well as in macrostructures and large periodic structures. The book is dedicated to Prof. Dr. Dr. hc. Peter Russer and his research work which is shown in his autobiography.
elib2cris::1512001600,weigel2011